Condicionantes democráticas da comunicação social : constitucionalidade das restrições judiciais prévias à liberdade de expressão - Cerqueira, Ermelino Costa (2015)
Based on the analysis of the interdependence between the concepts of democracy and the public sphere, this study investigates the reach of the fundamental right to freedom of expression, especially when conducted through media communication and their chances of litigation, distinctively when it occurs by an inhibitory guardianship that forbids the act of communicating. To that end, the procedural conceptions of democracy developed from the mid-twentieth century by Joseph Schumpeter, Norberto Bobbio, Robert Dahl, Boaventura de Souza Santos and Jürgen Habermas are initially addressed. Each conception emphasizes the role of freedom of expression and its relevance to the public sphere formation, whose concept and assumptions displayed in the works of the aforementioned authors are used for establishing the essential conditioning factors to the media democratic setting. Under these parameters, the study explores the constitutional system of freedom of expression and of media and its Supreme Federal Court interpretation through the decision that declared the former press law non-compatible by the Constitution of 1988, covering the latest court decisions that have attributed an absolute tone to freedom of expression according to a vast concept of censorship, eliminating almost completely from judicial consideration the product of media activity through an ultra-liberal argumentative standard that ignores the unequal and concentrated structure of communication freedoms operating instruments.